2011
DOI: 10.4028/www.scientific.net/amr.383-390.6116
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Engine Operating Parameters on Lean Combustion Limit of Hydrogen Enhanced Natural Gas Engine

Abstract: An experimental study was conducted on a S.I. engine fueled by compressed natural gas and hydrogen blends (HCNG), in order to test different engine operating parameters that affect lean combustion limit (L.C.L) of HCNG engine. Firstly, constant ignition timing and ignition timing under maximum L.C.L (L.L.T) conditions were compared, then L.L.T conditions were adopted in this paper. The results indicated that for each condition, neither over-retarded nor over-advanced ignition timing are advised in order to ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Owing to the large burning velocity and lower flammability limit, hydrogen is a candidate fuel for stabilizing lean operations and reducing emissions of natural gas engines [12][13][14][15]. For instance, Ma et al [12] reported that the excess air ratio of purely natural gas at 105 kPa of manifold absolute pressure was 1.71 and could be extended to 1.82, 2.09, and 2.4 by adding 10%, 30%, and 50% in volume fraction of H 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the large burning velocity and lower flammability limit, hydrogen is a candidate fuel for stabilizing lean operations and reducing emissions of natural gas engines [12][13][14][15]. For instance, Ma et al [12] reported that the excess air ratio of purely natural gas at 105 kPa of manifold absolute pressure was 1.71 and could be extended to 1.82, 2.09, and 2.4 by adding 10%, 30%, and 50% in volume fraction of H 2 , respectively.…”
Section: Introductionmentioning
confidence: 99%